2018
DOI: 10.1111/ejh.13036
|View full text |Cite
|
Sign up to set email alerts
|

miRNA‐15a, miRNA‐16, miRNA‐126, miRNA‐146a, and miRNA‐223 expressions in autologous hematopoietic stem cell transplantation and their impact on engraftment

Abstract: In conclusion, all investigated microRNAs changed significantly in the course of transplantation. Our results suggest that the miRNAs may participate in hematopoietic recovery in the early post-transplant period and influence engraftment efficiency after HSCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Biologic factors and processes influencing the behavior of hematopoietic cells during mobilization and transplantation have still not been fully discovered and understood; however, it is known that in the complex milieu of components participating in HSC maintenance, survival, proliferation, and differentiation [ 57 , 58 ], different elements such as adhesive molecules, growth factors, cytokines, proteases, miRNAs, and sirtuins are involved [ 59 , 60 , 61 ]. Among these factors, sirtuins may play an important role in the mobilization of HSCs through their deacetylating activity, which regulates many important processes related to the fate of HSCs, their metabolism, stress response, differentiation, aging, and apoptosis [ 62 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…Biologic factors and processes influencing the behavior of hematopoietic cells during mobilization and transplantation have still not been fully discovered and understood; however, it is known that in the complex milieu of components participating in HSC maintenance, survival, proliferation, and differentiation [ 57 , 58 ], different elements such as adhesive molecules, growth factors, cytokines, proteases, miRNAs, and sirtuins are involved [ 59 , 60 , 61 ]. Among these factors, sirtuins may play an important role in the mobilization of HSCs through their deacetylating activity, which regulates many important processes related to the fate of HSCs, their metabolism, stress response, differentiation, aging, and apoptosis [ 62 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…Patients with higher serum levels of miR-214 had extended overall survival upon bisphosphonate-based therapy ( 68 ). In patients with autologous stem-cell transplantation, the lower level of miR-15a on day 0 was associated with the shorter time to engraftment, and miR-20a decreased at complete remission ( 69 , 70 ). These results demonstrate that the expression patterns of circulating microRNAs are valuable markers for predicting treatment response.…”
Section: Discussionmentioning
confidence: 99%
“…We evaluated the kinetics of circulating miRNA-15a, miRNA-16, miRNA-126 and miRNA-146a as well as miRNA-223 in the group of patients with lymphoproliferative malignancies before autologous HSCT and early after transplantation [93]. We observed a…”
Section: High-level Expression Of Granulocyte-macrophage Progenitors mentioning
confidence: 98%
“…Expression of this miRNA is induced by the NF-κB protein complex, which plays a significant role in inflammatory response [90]. MiRNA-146a regulates mobilization of HSC as well as their homing after bone marrow transplantation [90][91][92][93]. Previous research has shown that under the influence of G-CSF, expression of CXCR4 chemokine receptor mRNA and protein in AML cells was decreased while the level of miRNA-146a was increased [94].…”
Section: Mirna-146amentioning
confidence: 99%